The Value Proposition of Sustainable Tourism - Ridho, Hatta; Harahap, Kartini; Thamrin, Husni; Daulay, Harmona; Siregar, Onan Marakali (International Journal of Architecture and Urbanism, 2026)
Sustainable tourism requires destination managers to maintain operational stability while balancing economic, social, and environmental priorities. In Indonesia, tourism supports community welfare and national economic development, yet since 2020 the sector has been disrupted by the Covid-19 pandemic, which reduced tourist visits, weakened local businesses, and decreased community income. Several destinations also face sustainability issues, including environmental pollution, inadequate safety management, and damaged facilities that may endanger visitors. This study aims to develop a systematic procedure for creating a sustainable tourism value proposition that improves business performance while strengthening social and environmental responsibility. A qualitative library research method was used through a literature review approach. Secondary data were collected from books, journal articles, government documents, institutional reports, and relevant online sources. The data were analyzed by comparing, differentiating, critically reviewing, synthesizing, and summarizing literature and empirical examples. The findings show that sustainable tourism value propositions can be developed through seven activities: identifying tourists, analyzing tourist needs, recognizing destination resources, examining value chain activities, controlling costs, determining value proposition dimensions, and applying sustainability indicators. These activities are realized through eleven dimensions: newness, performance, customization, getting the job done, design, brand or status, price, cost reduction, risk reduction, accessibility, convenience, and usability.